France in the Americas - Harvard College - Library (2021)
"A collection documenting the French presence in the Americas from the early 16th century through the 19th century. [...] Diplomatic, commercial, scientific, and cultural exchanges have fostered relationships between France and many countries around the world. The France in the Americas collection explores that shared history through a selection of thousands of handwritten and printed pages, photographs, and prints. Included in the collection are books, maps, and other distinctive materials pertaining to the early French exploration of North America, the French and Indian War, the American Revolution, and the Louisiana Purchase. Harvard Library holds hundreds of unique documents attesting to the interactions between France and the Americas. These materials are a rich resource for scholars and visiting researchers from around the world." [self-descfription]